Migration to Germany: Research questions and first results - Michael Fertig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2003)
Germany has been an immigration country for more than 30 years now, although many politicians persistently claim the opposite and many people in Germany are inclined to agree with their assessment. However, it is the actual experience with immigration, and not what people would like to experience nor legal or administrative definition, which qualifies a country as an immigration country. On this grounds it seems safe to argue that any assessment of Germany as no immigration country is far from reality. The well-documented (see. e.g. Schmidt 1996; Schmidt, Zimmermann 1992; 1995) history of immigration to Germany since the 1950s clearly suggests the conclusion that postWorldWar II-Germany in fact has been and still is an immigration country. Moreover, the German experience with immigration is not an isolated phenomenon. Since the end ofWorldWar II Europe as a whole which was an emigration region in the 19th century has made its way through a transition process to an immigration region (see e.g. Chiswick, Hatton 2001). In the course of this transition process Germany has become the main receiving country within Europe at least in absolute terms. The aim of this paper is to provide some evidence for this claim and to present some stylized facts on the German immigration record. Furthermore, it will be clarified how research on this experience in economics may be conceptualized in order to provide a common frame of reference for the contributions of this thesis to the received literature. This paper contains the introductory chapter of the author's doctoral thesis Germany as an Immigration Country - Empirical Evidence (University Heidelberg, 2002), it shows the structure of this thesis and main results. Clearly, the immigration experience of Germany poses a large number of research questions which have not been addressed yet. Moreover, all these research questions are of prominent relevance for economic as well as social policy. However, it is naturally beyond the scope of this thesis to provide answers to all or even the majority of these research questions. Contributions necessarily have to remain highly selective. However, it will be argued that all these research questions are intimately related and that a contribution to one of the open questions may hopefully be able to contribute to the research conducted in related areas in the future.
urn:nbn:de:101:1-200910131363
Keywords: 300